The heavy metal analysis of three Tinospora species frequently used in traditional medicine preparation sampled from different environmentally diverse locations (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
Herbal drugs have been used as remedies for the treatment of a large number of human ailments since ancient times as part of the traditional medicine system. Significant groups of the indigenous systems of medicine are based on herbal drugs. Of these herbal drugs, Tinospora cordifolia plays a vital role in treating various diseases and disorders. But nowadays, these plants are heavily contaminated with heavy metals. Heavy metal contamination in herbal medicines is a global threat to humans, especially at levels above known threshold concentrations. This investigation aimed to evaluate the concentrations of four heavy metals: cadmium (Cd), lead (Pb), arsenic (As) and mercury (Hg) in three Tinospora species: T. cordifolia, T. crispa and T. malabarica using inductively coupled plasma - optical emission spectrometry (ICP-OES). Samples were collected from environmentally diverse locations. Our investigation made it clear that T. crispa had the highest quantity of heavy metals, followed by T. malabarica and T. cordifolia. In most samples, mercury and arsenic were above the detection limit recommended by WHO. Warty tubercle samples of T. species had significantly higher amounts of heavy metal when compared to the rest of the parts tested. In addition to this, the samples collected from industry/urban areas recorded a considerable amount of heavy metals. These results suggest that T. cordifolia for formulation should be properly collected from wild/rural areas in order to avoid the accumulation of harmful heavy metals. Furthermore, it was suggested that the cultivation of medicinal plants should be curtailed near environmentally polluted areas, especially industrial areas, to avoid health hazards. Usually, T. malabarica and T. crispa will substitute or adulterate for T. cordifolia. So, identifying T. cordifolia is very important before going for ayurvedic formulations. The present study’s findings also highlight the need for relentless monitoring of heavy metal residues to ensure the quality and safety of finished herbal products.